Legal risk and investor protection for retail investment products: An empirical study of lawsuits regarding mutual funds and structured notes in Taiwan - CHEN, Christopher C. H. (Institutional Knowledge at Singapore Management University, 2015)
This article analyses the results of 322 lawsuits regarding retail mutual funds and structured notes in Taiwan between 2000 and 2012 and their relationship with other factors such as investors’ personal characteristics, main arguments and causes of action. This article has the following major findings: (1) the winning rate for investors was quite low, meaning that banks face low legal risk from misselling claims; (2) investors were not better off by filing a complaint to the Banker’s Association; (3) we have not proved the courts showing preference for investors with certain personal traits due to limited information available; (4) a plaintiff’s winning rate does not vary much from one argument to another, except for arguing formation of contract, but our research shows that more might have to be done to clarify post-contractual duty of banks; (5) there is also no proof showing that certain causes of action or litigation strategies would help investors winning a judgment and we have not proved that filing more causes of action would help to increate a plaintiff’s chance of winning. Our findings worth regulators and legislators to reconsider regulatory policies for investor protection as well as dispute resolution for financial consumers in the future to offer more complete protection of financial consumers.